Scoping review assessing the evidence used to support the adoption of mobile health (mHealth) technologies for the education and training of community health workers (CHWs) in low-income and middle-income countries - Winters, Niall (BMJ Open, 2018)
OBJECTIVES: Undertake a systematic scoping review to determine how a research evidence base, in the form of existing systematic reviews in the field of mobile health (mHealth), constitutes education and training for community health workers (CHWs) who use mobile technologies in everyday work. The review was informed by the following research questions: does educational theory inform the design of the education and training component of mHealth interventions? How is education and training with mobile technology by CHWs in low-income and middle-income countries categorised by existing systematic reviews? What is the basis for this categorisation? SETTING: The review explored the literature from 2000 to 2017 to investigate how mHealth interventions have been positioned within the available evidence base in relation to their use of formal theories of learning. RESULTS: The scoping review found 24 primary studies that were categorised by 16 systematic reviews as supporting CHWs’ education and training using mobile technologies. However, when formal theories of learning from educational research were used to recategorise these 24 primary studies, only four could be coded as such. This identifies a problem with how CHWs’ education and training using mobile technologies is understood and categorised within the existing evidence base. This is because there is no agreed on, theoretically informed understanding of what counts as learning. CONCLUSION: The claims made by mHealth researchers and practitioners regarding the learning benefits of mobile technology are not based on research results that are underpinned by formal theories of learning. mHealth suffers from a reductionist view of learning that underestimates the complexities of the relationship between pedagogy and technology. This has resulted in miscategorisations of what constitutes CHWs’ education and training within the existing evidence base. This can be overcome by informed collaboration between the health and education communities.